The effectiveness of health messages in countering advertising of unhealthy food : the role of regulatory fit - Yeo, Su Lin (2013)
Food consumption is a major contributing factor to the rise of obesity, with poor dietary patterns persisting despite public education on the importance of eating healthily. Health researchers have attributed the continued consumption of high-caloried foods to the cumulative exposure of television viewers to unhealthy food advertising. This has led some governments to impose regulations requiring unhealthy food advertisements to carry health messages. This research seeks to investigate the effectiveness of these health messages on attitudes and intentions related to unhealthy food consumption. A pre-study was first conducted to assess the amount of food advertising content on prime-time television in US, China and Singapore. A theoretical framework guided by the Regulatory Fit Theory was subsequently developed from the findings of the pre-study. It informed two quasi-experimental studies that tested two different formats - simultaneous and sequential - each presenting two sets of health messages alongside an unhealthy food commercial. The health messages were crafted to match either the individuals’ prevention or promotion regulatory orientation. Study 1 tested the effects of fit when both sets of health messages were presented in a simultaneous format; while Study 2 introduced an additional variable (message positioning) and tested the same sets of health messages in a sequential format. Results of Study 1 showed significant two-way interaction effects only for promotion-fit but not for prevention-fit on intentions to eat healthily. Study 2, on the other hand, found significant three-way interaction effects for both prevention- and promotion-fit and provides support for the moderating influence of message positioning on regulatory fit. Findings from the studies together with strategic considerations for health authorities are discussed. This research highlights the importance of regulatory fit and presentation formats of health messages on intentions to eat healthily and presents their implications for public health policy and intervention. It is hoped that the research findings will inform health practitioners in designing better public health campaigns.